Data on the effects of eIF6 downmodulation on the proportions of innate and adaptive immune system cell subpopulations and on thymocyte maturation - Nicola Manfrini; Sara Ricciardi; Annarita Miluzio; Maya Fedeli; Alessandra Scagliola; Simone Gallo; Thure Adler; Dirk H. Busch; Valerie Gailus-Durner; Helmut Fuchs; Martin Hrabě de Angelis; Stefano Biffo (Data in Brief, 2017)
The data described in this article are related to “High levels of eukaryotic Initiation Factor 6 (eIF6) are required for immune system homeostasis and for steering the glycolytic flux of TCR-stimulated CD4+ T cells in both mice and humans” (Manfrini et al., in press) [1]. eIF6 is a translation initiation factor required for ribosomal biogenesis (Sanvito et al., 1999) [2] and for proper translational initiation (Gallo and Manfrini, 2015; Miluzio et al., 2016) [3,4] whose protein abundance requires tight regulation. Here we analyze by flow cytometry the effects of eIF6 depletion on proportions of specific innate and adaptive immune system subpopulations and on thymocyte maturation in mice.